Hierarchically engineered Cu2O/CuO-coated Cu mesh for high-performance solar-driven water purification and energy harvesting - Animesh Roy; Muhammad Zakria Tariq; Moonwoo La; Dongwhi Choi; Sung Jea Park (Journal of Water Process Engineering, 2026)

Vitamin D Promotes Neuronal Survival via Nrf2 Upregulation in D-Galactose–Induced Mice: An In-Vivo and In-Silico Study - Fawad Ali Shah; Muhammad Zakria; Faten F. Bin Dayel; Najeeb Ur Rehman; Sarwat Jahan; Muhammad Ikram (Journal of Neuroimmune Pharmacology, 2026)

Repurposing spent battery waste into plasmonic photothermal membrane for efficient solar-driven evaporation and freshwater production - Muhammad Zakria Tariq; Animesh Roy; Byungki Kim; Youn-Hee Han; Sang-Youn Kim; Bong-Kee Lee; Sung Jea Park (Journal of Environmental Management, 2026)

Schiff Base Functionalized Adsorbent for Lead Removal from Contaminated Water and its Potential Regeneration Strategies for Re-Use - Muhammad Zakria; Mumtaz Ali; Muhammad Arshad; Jae-Woo Park; Min Jae Ko; Hassan Anwer (Water, Air, & Soil Pollution, 2026)

Ambroxol’s Role in PTZ-Induced Anxiety-Like Conditions in Mice: Targeting Neuroinflammation and Oxidative Stress via In Vivo and In Silico Approaches - Hafeeza Zafar Ali; Sarwat Jahan; Laila Ilahi; Sami Siraj; Muhammad Zakria; Najeeb Ullah; Muhammad Ikram; Ashraf Ullah Khan; Manzoor Khan; Fawad Ali Shah; Hafsah Muhammad (Molecular Neurobiology, 2026)

Correction: Emodin, a Potent Anthraquinone Mitigates MPTP-Induced Parkinsons’ Disease Pathology by Regulating Nrf2 and Its Downstream Targets: In Silico and In Vivo Approach - Sarwat Jahan; Muhammad Ikram; Sami Siraj; Shakir Ullah; Muhammad Zakria; Nasir Ahmad (Molecular Neurobiology, 2025)

Genetic Variability Among Isolates of Curvularia lunata and Exserohilum rostratum Causing Brown Leaf Spot of Rice from Pakistan - Muhammad Faizan Anwar Khan; Abid Riaz; Rafia Ahsan; Ishaq Ahmad; Saif Ullah; Ahmed Raza; Muhammad Zakria (Current Microbiology, 2025)

Emodin, a Potent Anthraquinone Mitigates MPTP-Induced Parkinsons’ Disease Pathology by Regulating Nrf2 and Its Downstream Targets: In Silico and In Vivo Approach - Sarwat Jahan; Muhammad Ikram; Sami Siraj; Shakir Ullah; Muhammad Zakria; Nasir Ahmad (Molecular Neurobiology, 2025)

Synthesis and Antibacterial Studies of Silver Loaded TiO2 Electrospun Nanofibers Against E. coli by Fluorescence Spectroscopy and Microscopy - Bisma Khanam; Rafaqat Ali Khan; Shahzad Anwar; Hina Ali; Muhammad Zakria; Taj Muhammad Khan; A. Rahman; Ahmad Adnan; Nida Ali Shan; Muhammad Raffi (Journal of Fluorescence, 2025)

Optimized preparation of alginate/nanocellulose/polypyrrole composite hydrogel via in-situ polymerization for high-efficiency solar desalination and wastewater purification - Muhammad Faris Hamid; Balamurugan Karuppaiah; Muhammad Zakria Tariq; Moonwoo La; Dongwhi Choi; Sung Jea Park (Chemosphere, 2025)

Stripe rust resistance in historical wheat cultivars at seedling and adult plant stages and tagging effective resistance genes using molecular markers - Khawar Majeed; Muhammad Sufyan; Kainat Abbasi; Rafia Ahsan; Hadi Bux; Muhammad Zakria; Muhammad Fayyaz; Javed Iqbal Mirza; Mohsin Ali; Awais Rasheed; Zhonghu He (Journal of Plant Pathology, 2025)

Antibacterial Efficacy of Tryptophan Coordinated Silver Nanoparticles Against E. coli: Spectroscopic and Microscopic Evaluation of Bacterial Cell Death - Rafaqat Ali Khan; Shahzad Anwar; Hina Ali; Uzma Aziz; Bisma Khanam; Muhammad Zakria; Muhammad Raffi (Journal of Fluorescence, 2024)

Reduced graphene oxide supported polyaniline/copper (II) oxide nanostructures for enhanced photocatalytic degradation of Congo red and hydrogen production from water - Mohsin Raza Dustgeer; Asim Jilani; Mohammad Omaish Ansari; Muhammad Bilal Shakoor; Shafaqat Ali; Aniqa Imtiaz; Hazirah Syahirah Zakria; Mohd Hafiz Dzarfan Othman (Journal of Water Process Engineering, 2024)

3D carbonized orange peel: A self-floating solar absorber for efficient water evaporation - Animesh Roy; Muhammad Zakria Tariq; Moonwoo La; Dongwhi Choi; Sung Jea Park (Desalination, 2024)

Synergistic effect of electrochemically fabricated polyaniline nanofibers and silver for efficient solar steam generation - Animesh Roy; Muhammad Zakria Tariq; Moonwoo La; Dongwhi Choi; Sung Jea Park (Desalination, 2023)

Retraction notice to “Melatonin rescues the mice brain against cisplatin-induced neurodegeneration, an insight into antioxidant and anti-inflammatory effects” [Neurotoxicology 87 (2021) 1–10] - Muhammad Zakria; Nasir Ahmad; Lina Tariq Al Kury; Abdullah Alattar; Zia Uddin; Sami Siraj; Shakir Ullah; Reem Alshaman; Muhammad Imran Khan; Fawad Ali Shah (NeuroToxicology, 2023)

Removal of bisphenol A from synthetic and treated sewage wastewater using magnetron sputtered CuxO/PVDF thin film photocatalytic hollow fiber membrane - Hazirah Syahirah Zakria; Mohd Hafiz Dzarfan Othman; Roziana Kamaludin; Asim Jilani; Muhammad Firdaus Omar; Muhammad Ayub; Muhammad Abdul Razis Saidin; Tonni Agustiono Kurniawan; Norbaya Hashim; Nasehir Khan E.M. Yahaya; Nirmala Devi A/P Kerisnan@Kerishnan; Alias Mohammed (Journal of Water Process Engineering, 2023)

Influence of temperature on the development and reproduction of Spodoptera litura (Fabricius) on castor bean: implications for its use as a trap crop - Muhammad Zakria; Muhammad Shah Zaib; Khalid Abbas; Muhammad Sarmad; Syed Muhammad Zaka; Muhammad Noor-ul-Ane (Arthropod-Plant Interactions, 2022)

Investigation of antifungal response of NiO and copper-doped NiO thin films against Aspergillus niger and Macrophomina phaseolina fungi - Muzamil Aftab; Muhammad Zakria Butt; Dilawar Ali; Zille Huma Aftab; Muhammad Usman Tanveer; Bakhtawar Fayyaz (Environmental Science and Pollution Research, 2022)

Groundwater and soil salinity variations in a canal command area in Pakistan - Muhammad Latif; Muhammad Zakria Ahmad (Irrigation and Drainage, 2009)
This three‐year study was undertaken to investigate the groundwater and soil salinity variation in a canal‐irrigated area. Water and soil samples were collected along 54 tertiary canals located on six secondary canals (two each at head, middle and tail end) of a main canal. Data of crop yield and income of the farmers were also collected. The results show that electrical conductivity (EC) of groundwater increased from head to lower reaches along all the irrigation channels, i.e. main, the secondary and the tertiary canals. Similarly, the soil water EC e also increased with increased distance from the head of the irrigation system. Reduced canal water supply at lower reaches of the irrigation system forced the downstream water users to pump more groundwater, thereby increasing their irrigation cost. The deteriorating groundwater quality further adds misery to the downstream farmers by degrading productivity of their lands caused by excessive use of saline groundwater. Location of the water users along the canal irrigation system had an impact on their crop yield as well as income and these parameters decreased with increased distance from the head of the irrigation channels. For example, the net income of the tail‐end farmers varied from 43% to 59% of the head‐end farmers. Copyright © 2008 John Wiley & Sons, Ltd.

Infection and colonization of aseptically micropropagated sugarcane seedlings by nitrogen-fixing endophytic bacterium, Herbaspirillum sp. B501gfp1 - Joyce Njoloma; Kazunori Tanaka; Tasuku Shimizu; Tomohiro Nishiguchi; Muhammad Zakria; Ryo Akashi; Moriya Oota; Shoichiro Akao (Biology and Fertility of Soils, 2006)